Two-dimensional modeling the static parameters for a submicron field-effect transistor - Zaabat, M.; Draid, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
A comparison of two different models for simulation of submicron GaAs MESFETs static characteristics has been made. A new two-dimensional numerical model is presented to investigate the submicron field-effect transistor characteristics, the influence of the geometry of the component, like the inter-electrode distance, on the capacities. All simulation revealed the existence of a high contact electric field near the gate, which creates a depopulated zone around the gate, but the preceding studies have neglected the edge effects, which are very significant for the submicron MESFETs.